Matisse in Nice
In 1917, Henri Matisse Chose to leave the comfort and critical acclaim he had achieved in Paris to live in Nice. There he settled in a modest hotel room on the french Riviera and began to create paintings unlike any he had previously produced. Over the next Thirteen years, the painter responded the profoundly to the Mediterranean and the constancy of its ligth. At the same time that Matisse depicted the open landscape around Nice he explored the privacy of richly patterned interiors